1990
DOI: 10.1073/pnas.87.8.3057
|View full text |Cite
|
Sign up to set email alerts
|

Human trophoblast-extracellular matrix (ECM) interactions in vitro: ECM thickness modulates morphology and proteolytic activity.

Abstract: Trophoblast invasion of the uterine extracellular matrix, a critical process for human implantation and uteroplacental vascular development, is a striking example of controlled invasiveness. To examine cellular behavior relevant to this process, human trophoblasts were cultured on (a) Millicell filters prelayered with Matrigel and (it) coverslips precoated with a gentle slope of Matrigel (Matribeach). Histologic sections of the Millicell system demonstrated significant invasion. However, on Matribeach the cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
49
2
1

Year Published

1991
1991
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(53 citation statements)
references
References 14 publications
(24 reference statements)
1
49
2
1
Order By: Relevance
“…Human CTBs are able to invade amniotic membranes [37] and Matrigel invitro [38][39][40], and to digest ECM [5]. This behavior is clearly related to secreted metalloproteinases, as TIMP expression inhibits their invasiveness [37].…”
Section: Proteasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Human CTBs are able to invade amniotic membranes [37] and Matrigel invitro [38][39][40], and to digest ECM [5]. This behavior is clearly related to secreted metalloproteinases, as TIMP expression inhibits their invasiveness [37].…”
Section: Proteasesmentioning
confidence: 99%
“…Preeclampsia is characterized by a decreased expression of HGF by the stroma of the villi [78]. Protein kinase C activators such as phorbol esters increase in vitro trophoblast invasion [38] and secretion of MMP-9 [79]. The activity of MMP-9 is upregulated by leptin and IL-1α [73,80], and it is known that IL-1 concentrations in embryo culture medium are correlated with success of in vitro fertilization procedures [81].…”
Section: Hormones and Cytokinesmentioning
confidence: 99%
“…As a result, the embryo will be anchored in the maternal uterus and uteroplacental arteries will be invaded, leading to the dilation of the vessel lumina, which is necessary to enhance uterine and intervillous blood flow in pregnancy. There are striking similarities between invasive cytotrophoblasts and invasive cancer cells (Kliman and Feinberg, 1990;Murray and Lessey, 1999;Bischof and Campana, 2000;Bilban et al, 2000;Murray and Lessey, 1999;McMaster et al, 1998). However, in contrast to tumor invasion, interactions between trophoblasts and uterine cells are closely regulated both temporally and spatially by mechanisms that are largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Human term gestational tissues express all components of the PA cascade and undergo extensive ECM remodeling at the time of labor and delivery (Feinberg et al 1989;Granstrom et al 1989Granstrom et al ,1991Granstrom et al ,1992Kliman and Feinberg 1990;Hofmann et al 1994;Kliman 1994). It has been suggested that localized degenerative changes in the amnion and chorion may be sufficient to reduce tensile strength and hence mediate fetal membrane rupture at term (Vadillo-Ortega et al 1995).…”
mentioning
confidence: 99%